Antiinflamasi Ekstrak Daun Trembesi (Samanea saman (Jacq.)Merr.) Terhadap Ekspresi Enzim Siklooksigenase-2 (COX-2) - Sa'adah, Nikmatus; Lukis, Prima Agusti; Asri, Arilis Larasati Ode; Istiati, Istiati; Asmarani, Yolanda Kartika; Moelok, Iqbal Moch; Adriansyah, Agus Aan; Setianto, Budhi (LPPM, Institut Teknologi Sepuluh Nopember, 2024)
Background: The cyclooxygenase-2 (COX-2) enzyme is the main source of prostanoids in inflammation and has various effects on nerve endings, blood vessels, and cells involved in inflammation. Trembesi leaves (Samanea summons (Jacq.) Merr.) are one of the herbal plants that have anti-inflammatory properties because it contains steroid compounds with high antioxidant capacity, active compounds of flavonoids, and tannins. With antioxidant activity and high flavonoid, trembesi leaf extract can act as an anti-inflammatory and influence the COX-2 enzymes and can cause pro-inflammatory effects. Objective : To discover the effect of trembesi leaf extract as an anti-inflammatory on COX-2 enzyme levels. Laboratory experimental method live with 30 (Rattus norvegicus) with 3 sample groups: the negative control group was CMC NA, and the treatment group was given trembesi leaf extract 100 mg/KgBW and a dose of 200 mg/KgBW. COX-2 expression was examined using the immunohistochemical staining method. Then do data analysis with normality test, homogeneity test, test Kruskal-Wallis, and test Mann Whitney. Results : Trembesi leaf extract at a dose of 100 mg/KgBW with a concentration of 12% had the effect of inhibiting COX-2 enzyme expression compared to the negative control group and the extract group at a dose of 200 mg/KgBW at a concentration of 12%. Conclusion : Trembesi leaf extract has an effect on reducing inflammation of the cyclooxygenase-2 (COX-2) enzyme.